Analisis kemampuan berpikir kritis dalam materi interaksi sosial pada pembelajaran IPS kelas V sekolah dasar - Indiarti, Candra Laelika; Poerwanti, Jenny Indrastoeti Siti; Sularmi, Sularmi (Didaktika Dwija Indria, 2022)
The purpose of this study was to describe the analysis of students' critical thinking skills in social interaction material in social studies learning for class V SD Negeri Bojong 03, Kawunganten District, Cilacap Regency for the 2021/2022 academic year. This research is a qualitative descriptive study. The data sources of this research include the results of students' thinking ability tests, the results of student and teacher interviews, and documentation of the results of students' answer sheet. The subjects in this study were 3 students who were selected using a purposive sampling technique. Data collection techniques using tests, interviews, and documentation. The data validity test technique used triangulation. The data analysis technique in this qualitative research uses data analysis techniques using the Miles and Huberman model which consists of collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the percentage of explanation indicators was 55.56%, interpretation indicators 77.78%, analysis indicators 55.56%, evaluation indicators 66.67%, inference indicators 55.56%, and self-regulation indicators 88.89%. The most dominant indicator is self-regulation indicator. While the lowest indicators are three indicators, namely explanation, analysis and inference. The average percentage of critical thinking skills of fifth grade students at SD Negeri Bojong 03 Kawunganten is 66.67%. Based on this percentage, it can be said that the analysis of critical thinking skills of fifth grade students at SD Negeri Bojong 03 Kawunganten is in the medium category.Keywords: critical thinking skills, elementary school